Altered electrophysiology mechanism related to inhibitory control in adults with insomnia - Ding, Xiaobin; He, Liang; Geng, Xicong; Zhao, Xuan; He, Zijing; Zhang, Xiangzi (Frontiers in Neurology, 2023)
Insomnia disorder (ID), one of the most common psychophysiological disorders, can put a serious burden on the individual's work and academic performance. Cognitive dysfunction often exists in patients with insomnia, which negatively affects their quality of life. Inhibitory control (IC), as a vital cognitive function, allows individuals to suppress attention, behavior, or thoughts that are irrelevant to the task, so as to effectively adapt to the current goal. The earlier studies on the inhibitory control of insomnia patients predominantly used subjective scales for evaluation, and that can have drawbacks because they do not provide an objective assessment. In order to investigate the inhibitory control function of individuals with insomnia, this research subdivides inhibitory control into response inhibition and conflict inhibition. Response inhibition and conflict inhibition capacities of individuals with insomnia were evaluated using the two-choice oddball task and the color-word stroop task, and accordingly the association between insomnia disorder and inhibitory control capacity, as well as its cognitive neural mechanism, was examined. Finding behavioral results, individuals with insomnia conducted the two-choice oddball test and the color-word stroop task with lower accuracy and slower reaction times compared to healthy sleepers. The ERP results found, when performing the two-choice oddball task, the P3 amplitude of the individuals with insomnia was significantly lower than that of the healthy sleepers while there was no significant difference between the N2 amplitudes of the two groups. At the same time, when completing the color-word stroop task, the N450 amplitude of individuals with insomnia was significantly lower than that of healthy sleepers. These findings suggest that in response inhibition tasks, individuals with insomnia may have weaker motor inhibition abilities and similarly perform weaker conflict monitoring abilities in conflict inhibition tasks, which indicates that individuals with insomnia' inhibitory control is impaired compared to that of healthy sleepers. Thus, this study is related to the finding at the electrophysiological level that there is a certain correlation between insomnia and a decline in inhibitory control ability, which may suggest that improving inhibitory control function in patients with insomnia is a clinically significant and worthwhile area of adjuvant treatment.